If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 + 15w = 3w + -1w + 4w Combine like terms: 3w + -1w = 2w 33 + 15w = 2w + 4w Combine like terms: 2w + 4w = 6w 33 + 15w = 6w Solving 33 + 15w = 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 33 + 15w + -6w = 6w + -6w Combine like terms: 15w + -6w = 9w 33 + 9w = 6w + -6w Combine like terms: 6w + -6w = 0 33 + 9w = 0 Add '-33' to each side of the equation. 33 + -33 + 9w = 0 + -33 Combine like terms: 33 + -33 = 0 0 + 9w = 0 + -33 9w = 0 + -33 Combine like terms: 0 + -33 = -33 9w = -33 Divide each side by '9'. w = -3.666666667 Simplifying w = -3.666666667
| 3t^2+8=t^2-3t-12 | | -20n=-60 | | 9+9x-3= | | 8+14r-7=8r+49-6r | | 24-7x=-3+28-7x | | 8-(4z-1)=2-5z | | 2x^2-5x-19=-7 | | y=-.02x+0.14 | | 0.1x^2-0.1x=0.3 | | 33+15w=3w-1w+4 | | Factor(5x^2-11x+4)=0 | | 3(y+9)=2y | | 8m-16=-23+m | | 2x(x+4)=4(5-3x) | | -9x=-4(6) | | 4x(x+5)+10(x+1)=24 | | (5x^2-11x+4)=0 | | n^2+P^2=y^2 | | -9(3-2y)+8y=-23 | | 28x^2-343=0 | | (5x^2-11+4)=0 | | 9*0+2= | | 4y+3-2y=9+y-4 | | 18.5+2.25a=47.75 | | 9x+2=-34 | | -2(2)+y=-2 | | 4x^2+29x+15=8 | | 4(x-4)+6=4x+9 | | 10(t+3)-4y= | | -3(t-6)-2(2t+1)=-5 | | -2-7(n+2)=-20-7n | | -2(t-6)-2(2t+1)=-5 |